“Self-Motivated Attitude, Judgment, Inspiration, Exploration, and Construction among Secondary School Students through STEAM Education with Reference to the Role of Teacher.” (International Journal of Food and Nutritional Sciences, 2021)
The research article is written by the author keeping in view the prominence of STEAM Education in every secondary school of Kashmir valley, as it is very important to inculcate the scientific temper and sensitivity towards technology among the student as early as possible. In our Schools, we believe that the role of a teacher is to initiate students to energetically discover and continue their education. Teachers should plan the curriculum which is fully loaded with insightful views and leveraging technology. On daily basis learning, students will be able to go into the diverse areas with self-confidence and understanding in non-traditional thinking with the introduction of STEAM Education. As STEAM Education is a Self-motivated attitude, judgment, inspiration, exploration, and construction. These five distinctive features are important as they include inner and outer essentials of an attitude that endorse development among the secondary school students. It should be introduced as early as possible in every secondary school of the valley, like in every distinctive secondary schools where students are involved in the projects. All the students enthusiastically use dynamic innovation and engineering approaches, which brought in them the development like questioning and intuitive imagination. This progressive way of learning can helps to generate a new kind of educational format where pupils from the very beginning get optimistic approach to take risks and undertaking their ideas. At the end author has write down certain suggestions how to inculcate the Self-motivated attitude, Judgment, inspiration, exploration, and construction through STEAM Education among Secondary school Students and how to instil the sensitivity towards STEAM Education.